Reimagining Arabic Language Instruction Through Visual Wall Charts: Insights from an Indonesian Madrasah Experience - Nur Azizah; Luthfiyah Khoirun Nisa; Naifah Naifah (Learning, Media and Technology in Arabic Education, 2025)
Background of study: The teaching of Arabic in Indonesian schools often encounters difficulties, particularly in capturing students’ interest and helping them understand the material. These problems are closely tied to the language’s perceived complexity and the lack of interactive media in the classroom. Aims and scope of paper: This study set out to explore how wall chart media “simple yet visually engaging tools” can support the Arabic learning process. Specifically, it examined whether these visual aids could foster greater student motivation, enhance understanding, and encourage participation during lessons. Methods: A qualitative case study was conducted at MA NU 03 Sunan Katong. The data were gathered through direct classroom observations, teacher and student interviews, and documentation review. Thematic analysis was applied to identify meaningful patterns, supported by source triangulation for credibility. Result: The study revealed that students responded positively to the use of wall charts. They felt more involved in learning activities, and complex topics became easier to grasp through clear visual explanations. Teachers also reported smoother lesson delivery and livelier classroom interactions. Academic outcomes showed noticeable improvement when wall charts were integrated into teaching. Conclusion: Wall charts offer a practical and effective solution for improving Arabic language instruction, particularly in settings where resources are limited. Beyond their educational value, these visual tools contribute to a more vibrant and student-centered learning environment.